Colposcopy telemedicine: live versus static swede score and accuracy in detecting CIN2+, a cross-sectional pilot study - Katayoun Taghavi; Dipanwita Banerjee; Ranajit Mandal; Helena Kopp Kallner; Malin Thorsell; Therese Friis; Ljiljana Kocoska-Maras; Björn Strander; Albert Singer; Elisabeth Wikström (BMC, 2018)
Abstract Background This cross-sectional pilot study evaluates diagnostic accuracy of live colposcopy versus static image Swede-score evaluation for detecting significant precancerous cervical lesions greater than, or equal to grade 2 severity (CIN2+). Methods VIA or HrHPV positive women were examined using a mobile colposcope, in a rural clinic in Kolkata, India. Live versus static Swede-score colposcopy assessments were made independently. All assessments were by gynecologists, junior or expert. Static image assessors were blinded to live scoring, patient information and final histopathology result. Primary outcome was the ability to detect CIN2+ lesions verified by directed biopsies. Diagnostic accuracy was calculated for live versus static Swede-score in detecting CIN2+ lesions, as well as for interclass correlation. Results 495 images from 94 VIA positive women were evaluated in this study. Thirteen women (13.9%) had CIN2+ on biopsy. No significant difference was found in the detection of CIN2+ lesions between live and static assessors (area under curve = 0.69 versus 0.71, p = 0.63). A Swede-score of 4+, had a sensitivity of 76.9% (95% CI 46.2-95.0%) and 84.6% (95% CI 54.6-98.1%), for live- and static-image assessment respectively. The corresponding positive predictive values were found to be 90.9% (95% CI 75.7-98.1%) and 92.6% (95% CI 75.7-99.1%). The interclass correlation was good (kappa statistic = 0.60) for the senior static assessors. Conclusions Swede-score evaluation of static colposcopy images was found to reliably detect CIN2+ lesions in this study. Larger studies are needed to further develop the colposcopy telemedicine concept which may offer reliable guidance in management where direct specialist input is not available. Trial registration Ethical approval of the study was obtained by the Chittaranjan National Cancer Institute (CNCI) Human Research Ethics Committee (4.311/27/2014). The trial was retrospectively registered in the Clinical Trails Registry of India CTRI/2018/03/012470.